Inscriptions of Sumatra; II. Short epigraphs in Old Javanese - Griffiths, Arlo (Wacana, Journal of the Humanities of Indonesia, 2012)
This article documents the existence of inscriptions using Old Javanese language on the island of Sumatra, by editing three short epigraphs, the first of which has previously been published but never satisfactorily interpreted, while the remaining two have not yet been published at all. However short these texts are in themselves, they raise interesting questions about the cultural, commercial, political, and linguistic connections between Java and Sumatra in ancient times.